Hubungan Antara Health Belief Model dengan Perilaku Kepatuhan Kebijakan Pembatasan Sosial Berskala Besar (PSBB) Selama Pandemi COVID-19 pada Emerging Adult (SUKMA : Jurnal Penelitian Psikologi, 2020)
In December 2019, COVID-19 declared by WHO as a global pandemic caused by a new type of corona virus or SARS-CoV2. During a pandemic, effective drugs and treatments are not always available because the virus attacks are massive. To overcome this, World Health Organization (WHO) recommends everyone protect themselves from the virus by carrying out healthy behaviors such as meeting room restrictions and quarantine areas as a preventive measure. However, in practice some people do not adhere to the recommended health behavioral policies causing the number of infected people is increasing. The purpose of this study is to look at the relationship of community compliance towards  Pembatasan Sosial Berskala Besar (PSBB) policy and Health Belief Model. Health Belief Model can explain how individuals perceive a health behavior and whether they are willing to implement it. The sampling technique used were purposive sampling which got 159 respondents who were in the emerging adult period and were domiciled in the three most affected provinces of COVID-19: DKI Jakarta, West Java and East Java. This research uses spearman test. The results of the analysis with the Spearman correlation n = 159 is Health Belief Model has positive significant  relationship with compliance.Keywords : Health Belief Model, Compliance, COVID-19, Pembatasan Sosial Berskala Besar (PSBB), Emerging Adult